Hepatitis A virus strains identified in jogaejeot associated with outbreaks in Seoul, South Korea. (5th May 2021) - Jeong, H.W.; Kim, M.K.; Yi, H.J.; Kim, D.M.; Jeon, S.J.; Lee, H.K.; Oh, Y.H.; Hwang, Y.O.
Abstract: Jogaejeot, seasoned Venerupis philippinarum, is a traditional Korean fermented food, and hepatitis A virus (HAV) can be transmitted through contaminated food, especially bivalve shellfish, causing acute gastroenteritis worldwide. Here, we carried out a phylogenetic analysis to identify and characterize HAV strains in jogaejeot samples associated with hepatitis A (HA) outbreaks in Seoul, South Korea, in 2019. The HAV strains were identified using blast and molecular analysis of the amplified HAV VP1‐P2B genome region. The HAV strains identified in the five jogaejeot samples shared at least 99% sequence identity, were all classified as genotype IA and were most closely related to strains that are widespread in East Asia. These results support a link between the consumption of jogaejeot and the HA outbreaks observed in 2019 in Seoul. In addition, they indicate a need for more stringent enforcement of food safety regulations for the shellfish industry, especially against HAV, and the value of widespread vaccination. Abstract : Significance and Impact of the Study: In 2019, a surge in acute hepatitis A (HA) in Seoul, South Korea, was believed to have been caused by jogaejeot. In this study, we were the first to find that HA virus strains were genetically similar among jogaejeot samples consumed during that period, supporting the assumption that jogaejeot samples were the common cause of the 2019 HA outbreak. We expect that these data will be used to improve shellfish food safety regulations.